PERSEPSI MAHASISWA AKUNTANSI TERHADAP ETIKA BISNIS DAN ETIKA PROFESI DI PANDANG DARI SEGI GENDER (Studi Kasus Mahasiswa Akuntansi Unisma) - Ilma Suryani Mardana; Junaidi Junaidi; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This research focuses on business ethics and professional accounting ethics using empirical studies at the University of Islam Malang. The purpose of this study was to examine the average difference in perceptions of business ethics and professional accounting ethics between male and female accounting students at the University of Islam Malang. The population of this study were accounting students at the University of Islam Malang. The sample used was 56 respondents consisting of 28 male students and 28 female students. Data were collected using questionnaires and distributed by purposive sampling method. Independent sample t-test was used in testing this hypothesis. The results of the hypothesis show that there is no difference in the mean perception between male students and female accounting students of business ethics and accounting professional ethics.Keywords: Perception of accounting students, Business Ethics, Professional Ethics of accountants.